Análise de desempenho econômico da produção orgânica de leite em uma propriedade no Distrito Federal - Andréa Amaral Alves (2006)
With the worsening of the environmental crises there is un crease of action to give a new directions to the current productive processes. One of the major challenges of the modern agriculture consists in matching properly the food production to the increasing demands of the population and at the same time keeping the sustainability and the environmental preservation, thus guaranteeing the natural resources maintenance for the next generations. The organic agriculture advises about diversification and sustainability as well as the search for economic feasibility. For the evaluation of such economic feasibility, data from the farm called “Malunga” (a farm at the Federal District) were appraised, between 2002 and 2004. The results of Net Operating Revenue (NOR) displayed a positive general average per liter of milk for the three years taken in account, considering the milk price at R$ 0.40 (being the historical price of the conventional milk in that region) and at R$ 0.80 (being the historical price of organic milk in that region). The productivity indicators were similar to those observed in traditional properties. Therefore, the higher prices paid for the differentiated product can become an attractive factor for moving to the organic system, turning out to be an option for the familiar agriculture.